2022
DOI: 10.1021/acs.nanolett.2c03223
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Probabilistic Computing with Stochastic Perovskite Nickelates

Abstract: Probabilistic computing has emerged as a viable approach to solve hard optimization problems. Devices with inherent stochasticity can greatly simplify their implementation in electronic hardware. Here, we demonstrate intrinsic stochastic resistance switching controlled via electric fields in perovskite nickelates doped with hydrogen. The ability of hydrogen ions to reside in various metastable configurations in the lattice leads to a distribution of transport gaps. With experimentally characterized p-bits, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The maximum frequency observed in pristine NNO is 596 cm –1 (shown in SI Figure S6), while an oxygen dominated mode appears at 601 cm –1 in the H 0.25 NdNiO 3 system. While the frequencies associated with hydrogen motion are likely to strongly vary in this system with many metastable states, our calculations clearly indicate that vibrational modes with frequencies in excess of 700 cm –1 are associated with OH stretching modes. …”
Section: Resultsmentioning
confidence: 67%
“…The maximum frequency observed in pristine NNO is 596 cm –1 (shown in SI Figure S6), while an oxygen dominated mode appears at 601 cm –1 in the H 0.25 NdNiO 3 system. While the frequencies associated with hydrogen motion are likely to strongly vary in this system with many metastable states, our calculations clearly indicate that vibrational modes with frequencies in excess of 700 cm –1 are associated with OH stretching modes. …”
Section: Resultsmentioning
confidence: 67%
“…Metastability of states is both useful and presents a challenge depending on the application domain. For example, it has been reported that protons may take on multiple metastable configurations in a lattice, resulting in probabilistic transport gaps . The inherent probabilistic property of a device can be utilized to build p-bits that serve as building blocks for probabilistic computing.…”
Section: Computational Exploration Of Metastable Phasesmentioning
confidence: 99%
“…[78] (SOT). While many other implementations of p-bits are possible, from molecular nanomagnets [79] to diffusive memristors [80], RRAM [81], perovskite nickelates [82] and others, two additional advantages of the MRAM-based p-bits are the proven manufacturability (up to billion bit densities) and the amplification of room temperature noise. Even with the thermal energy of kT in the environment, magnetic switching causes large resistance fluctuations in MTJs, creating hundreds of millivolts of change in resistive dividers [70].…”
Section: Mixed-signalmentioning
confidence: 99%
“…Further improvements to hardware implementation include adaptive versions of PT [130] as well as sophisticated nonequilibrium Monte Carlo (NMC) algorithms [131]. Ideas involving overclocking p-bits such that they violate the t synapse ≪ ⟨T p-bit ⟩ requirement for further improvement [14] or sharing synaptic operations between p-bits [82] could also be useful. A combination of these ideas with algorithm-architecture-device co-design may lead to orders of magnitude improvement in sampling speeds and quality.…”
Section: Outlook: Algorithms and Applications Beyondmentioning
confidence: 99%